Prevalência de infecções de transmissão vertical: toxoplasmose, rubéola, hepatite B, sífilis, infecção pelo citomegalovirus e pelo vírus da imunodeficiência humana em gestantes atendidas em Caxias, Maranhão - Câmara, Joseneide Teixeira (2014)
The vertical transmission of infection from mother to child, and may increase morbidity and mortality of both mother and child, when not diagnosed and by suitably dealest, causing a serious public health problem. This study aimed to estimate the prevalence of antibodies to toxoplasmosis, rubella, cytomegalovirus, hepatitis B, syphilis and HIV among pregnant women in Caxias, Maranhão, Brazil and identify the main factors associated with seropositivity for Toxoplasma gondii infection in pregnant women attending two referral centers Caxias, MA. Descriptive, observational, cross-sectional study of 561 pregnant women who received prenatal care at two clinics reference to prenatal high risk in the period July 2011 to December 2012, the outpatient clinics of Maternity Carmosina Coutinho (MCC) and the Specialized Center for Maternal and Child Care (CEAMI). Serological tests for toxoplasmosis, rubella, cytomegalovirus, hepatitis B were performed by a laboratory conveniado to the municipality by the same trained technician, and for syphilis and HIV were performed in the Counseling and Testing Center (ATC) in the city laboratory. And a small sample of whole blood from five pregnant IGM reagent for Toxoplasma gondii and their respective newborns was processed at the Institute of Tropical Pathology and Public Health in the Department of Parasitology UFG for performing Polymerase Chain Reaction (PCR). Statistical analysis was performed using SPSS version 20.0 Windows, using the chi-square tests of association and Odds Ratio (95%CI), considering a significance level of 5%. It was found to be positive for HIV was 0.4%, 2.0% syphilis, rubella and cytomegalovirus IgG reactivity were 93.6% and 87.8% respectively without reactive IgM, HBsAg was negative for all pregnant women in the sample tested. Regarding toxoplasmosis in 437 (77%), 124 susceptibility (22.1%) and 5 (0.9%) women with active infection. Found no significant association between toxoplasmosis susceptibility and age, location, income, education, sewerage, number of pregnancies and gestational age. Variables with significant association (p≤0.05) were seropositive pregnant women who are multiparous (p=0.036), living with dogs stuck at home (p=0.001), and consumption of raw kibbeh (p=0.036). The frequency of seropositivity of these infectious diseases of vertical transmission in pregnant women seen at antenatal care in the city of Caxias-MA is considered high, but are similar to those described in other regions of Brazil. Pregnant women who are multiparous who perform consumption of raw kibbeh and live with dogs that do not wobble on the street, had more chance of becoming infected with Toxoplasma gondii, thus guidance on primary prevention measures and quarterly serological monitoring should be strengthened these infections of pregnant women, since it is important to identify and/or prevent congenital infection measured.